CLINICAL-ORIENTED TEACHING OF HUMAN ANATOMY: THE ROLE OF TOPOGRAPHIC AND FUNCTIONAL ANATOMY IN MEDICAL EDUCATION - Islamova Gulnara Raufovna (Modern American Journals, 2026)
Human anatomy plays a crucial role in the formation of clinical competence in medical students. However, insufficient integration of anatomical knowledge with clinical practice may limit students’ ability to apply theoretical concepts in real medical settings. This article examines a clinical-oriented approach to teaching human anatomy, emphasizing the importance of topographic and functional anatomy in medical education. The study is based on an analysis of contemporary educational literature and pedagogical practices focused on clinically relevant anatomy teaching. The findings suggest that integrating topographic and functional anatomy into the curriculum enhances students’ understanding of anatomical relationships, supports clinical reasoning, and improves readiness for clinical disciplines such as surgery, radiology, and internal medicine. A clinically oriented anatomy teaching model is therefore considered essential for improving the quality of medical education and bridging the gap between basic sciences and clinical practice.
Keywords: Clinical anatomy; topographic anatomy; functional anatomy; medical education; anatomy teaching methods